THE STUDENTS’ STRATEGY IN LEARNING ENGLISH VOCABULARY AT SMP METHODIST PANTAI LABU - Nainggolan, Gindo Tua; Asnawi, Asnawi; Santoso, Didik; Batubara, Irpan Apandi; Harianto II, Harianto II (PHILOLOGY Journal of English Language and Literature, 2025)
This study aims to identify vocabulary learning strategy used, analysis repetition strategy implementation, examine effectiveness on vocabulary retention, and formulate an adaptive model for local contexts. Using a qualitative case study approach, data were collected from one primary and three supporting informants through interviews, observations, document analysis, and stimulated recall sessions. Analysis revealed that the primary informant developed a sophisticated multi – modal repetition system with four techniques; temporal spacing, multi – modal reinforcement, contextual variation, and self- testing. Developments factors included prior learning experiences, parental influence, teacher methodology, and assessment patterns. Thematic analysis yielded five themes: systematic organization, multimodal implementation, metacognitive awareness, contextual influences, and strategy evolution. This research strategies gaps in literature by examining vocabulary learning in rural coastal schools, adaption of repetition strategies to local contexts, and integration of traditional strategies with innovative elements under limited technological resources. Findings contribute to developing more inclusive vocabulary learning models for diverse educational contexts in Indonesia.